Covalent organic frameworks embedding single cadmium sites for efficient carboxylative cyclization of CO2 with propargylic amines - Zhang, Yize; Li, Hangshuai; He, Xingyue; Wang, Aiqing; Bai, Guoyi; Lan, Xingwang (Green chemistry : an international journal and green chemistry resource : GC, 2023)
Converting CO2 into value-added chemicals over efficient and recyclable catalysts has attracted increasing attention. Covalent organic frameworks (COFs) have arisen as elegant heterogeneous catalysts for this subject. Herein, we report the synthesis of a crystalline 2,2′-bipyridine-based covalent organic framework bearing Cd single-atom sites (Cd-Bpy-COF) as a synergistic catalyst for the carboxylative cyclization under mild conditions with CO2 and propargylic amines. Periodically distributed bipyridine coordination units can anchor Cd single sites with high loading on the covalent organic framework, exposing large active surfaces to enhance the activity. The as-synthesized Cd-Bpy-COF exhibits excellent activity and outstanding stability for the carboxylative cyclization with CO2. Experimental and theoretical results demonstrate that the integration of COF framework and single Cd active sites remarkably boosts the adsorption and activation of CO2, and then promotes its following cyclization reaction. This study further demonstrates the designed possibility of COF catalysts at the molecular level for high-performance CO2 conversion.